Jeremiah's and Ezekiel's sign-acts - Friebel, Kelvin G., 1952- (Journal for the study of the Old Testament. Supplement series ;, 1999)
The books of Jeremiah and Ezekiel contain the majority of the biblical accounts of prophetic sign-actions. By analysing these two prophets' actions according to the terms and concepts used in studies of nonverbal communication and rhetoric, this work seeks to bring conceptual and terminological clarity to the discussion of prophetic sign-acts and to enhance the perception of the prophets as persuasive communicators. Rather than prophetic sign-acts being viewed as having a magical derivation or as being inherently efficacious in bringing about what they portray, the sign-acts are viewed as bein.